CLINICAL AND PARACLINICAL CHARACTERISTICS IN ELDERLY PATIENTS WITH COLONIC DIVERTICULITIS AT THONG NHAT HOSPITAL - Hữu Đức, Hồ; Văn Hưng, Nguyễn (Journal of Health and Aging, 2025)
This article analyzes the clinical and paraclinical features of 47 elderly patients with colonic diverticulitis at Thong Nhat Hospital. The majority were male (68.1%) and aged 60–74 (72.3%). The most common symptom was dull persistent abdominal pain (70.2%), mainly in the right and left iliac fossae. Fever and digestive disorders were atypical, with low fever rates (10.6%) and watery stools accounting for 51%. Blood tests showed leukocytosis in 46.8% and increased CRP in 93.6%. CT imaging was crucial for diagnosis and severity assessment, with 25.5% requiring surgery. The findings highlight the importance of recognizing atypical symptoms and the role of paraclinical tests in diagnosis in the elderly.